OPTIMALISASI PROGRAM KAMPUS MENGAJAR DALAM PENINGKATAN KUALITAS PENDIDIKAN SISWA DI SD NEGERI 8 BATUBULAN - Juniarta, I Kadek; Winaya, I Ketut; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2023)
The Teaching Campus Program is part of the Merdeka Belajar Kampus Merdeka (MBKM) which aims to improve the quality of student education through aspects of literacy and numeracy, technology adaptation and school administration. SD Negeri 8 Batubulan was appointed to implement the Teaching Campus program based on recommendations and criteria from the Directorate General of Higher Education. However, the implementation of the Teaching Campus program has so far encountered several obstacles such as limited facilities in supporting the implementation process of the Teaching Campus Program, socialization and supervision of the implementation of the Teaching Campus by relevant agencies in this case, namely educational institutions at the Regency to Provincial level, the level of student competence in the field education when implementing the Campus Teaching program. This study aims to optimize the implementation of the Teaching Campus program in improving the quality of student education at SD Negeri 8 Batubulan. The research method used in this research is descriptive qualitative. Data was collected by observation, interview and documentation methods. Based on the literature review, this study uses public policy theory with the concept of optimization according to Siringoringo (2005). The results of the study show that the objective indicators and alternative decision indicators have been running optimally, but the resource indicators that limit the aspects of human resources, support and support are still not optimal. The recommendations that can be given are Conducting special training, selection and intense debriefing for students before implementing the Campus Teaching program, Procurement and increasing the availability of facilities, infrastructure and facilities to support program implementation, and Increasing outreach to schools and supervisory functions carried out by related parties.